PRINCIPLE OF POLITENESS IN THE CHARACTERS OF THE FILM ANCIKA: DIA YANG BERSAMAKU 1995 BY PIDI BAIQ PRAGMATIC STUDY (Jurnal Ilmiah FONEMA, 2025)
Pragmatics is a branch of linguistics that studies the relationship between language and its context of use. This study aims to identify and describe the principles of politeness in the dialogues of characters in the film Ancika: Dia yang Bersamaku 1995 by Pidi Baiq. This research employs a qualitative descriptive method with content analysis techniques. The results show that there are 94 utterances containing all types of politeness maxims in the dialogues, with the approbation maxim being the most dominant, appearing in 24 utterances. Ten maxims according to Leech found in this study include the maxims of generosity, wisdom, approbation, modesty, apology, forgiveness, agreement, opinion, sympathy, and feeling. The dominance of the approbation maxim indicates a tendency of the characters to use polite language, praise, appreciate, and avoid direct criticism toward their interlocutors.